2020
DOI: 10.1186/s13018-020-01977-z
|View full text |Cite
|
Sign up to set email alerts
|

Poly(POG)n loaded with recombinant human bone morphogenetic protein-2 accelerates new bone formation in a critical-sized bone defect mouse model

Abstract: Background Delivery of bone morphogenetic protein-2 (BMP-2) via animal-derived absorbable collagen materials is used for the treatment of large bone defects. However, the administration of bovine proteins to humans is associated with the risk of zoonotic complications. We therefore examined the effect of combining BMP-2 with collagen-like peptides, poly(POG)n, in a critical-sized bone defect mouse model. Methods A 2-mm critical-sized bone defect was created in the femur of 9-week-old male C57/BL6J mice. Mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Bone graft fusion is an important factor affecting the efficacy of PVCR surgery. BMP can induce bone formation and irreversibly promote the differentiation of mesenchymal cells into chondrocytes and bone cells [12]. Among all BMP protein families, BMP2 and BMP9 have the strongest osteogenic ability; they can also induce the formation and deposition of calcium phosphate in bone, which is conducive to repairing bone and joint damage [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Bone graft fusion is an important factor affecting the efficacy of PVCR surgery. BMP can induce bone formation and irreversibly promote the differentiation of mesenchymal cells into chondrocytes and bone cells [12]. Among all BMP protein families, BMP2 and BMP9 have the strongest osteogenic ability; they can also induce the formation and deposition of calcium phosphate in bone, which is conducive to repairing bone and joint damage [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, the development of substitute materials such as the artificial bone has enabled ACDF with more material choices. Scholars have found that the recombinant human bone morphogenetic protein-2 (rhBMP-2) can accelerate the generation rate of cells, enhance the defect repairability of bone, and then fully optimize the effect of cervical interbody fusion [ 7 10 ]. It is an indisputable fact in academia that rhBMP-2 can improve the fusion rate of ACDF, but the optimal dosage is still not clear.…”
Section: Introductionmentioning
confidence: 99%